The Value of Political Ties Versus Market Credibility: Evidence from Corporate Scandals in China - Hung, Mingyi; Wong, T. J.; Zhang, Fang (Contemporary Accounting Research, 2015)
Abstract This paper compares the value of political ties and market credibility in China by examining the consequence of corporate scandals. We categorize Chinese corporate scandals by whether the scandal is primarily associated with the destruction of (i) the firm's political networks (political scandals), (ii) the firm's market credibility (market scandals), or (iii) both (mixed scandals). Consistent with our hypothesis that scandals signaling the destruction of political ties are associated with greater losses in firm value than scandals signaling the destruction of market credibility, we find that the stock market reacts more negatively to political and mixed scandals than to market scandals. In addition, the greater negative market reactions associated with political and mixed scandals are primarily driven by firms that rely more on political networks. We also find that, compared to market scandals, political and mixed scandals lead to larger decreases in operating performance, greater reduction in loans from state‐owned banks, and higher departure of political directors.